Synthesis and characterization of 5,6-diamino-1,10-phenanthroline substituted anti-dichloroglyoxime and its complexes with cobalt(II), nickel(II), and copper(II) - Demirhan, N; Erden, I; Avciata, U (MARCEL DEKKER INC, 2002)
In this study, a new dioxime ligand, 1,10-phenanthrolino(5,6-b)-2,3-dihydyroxyimino-1,4-diazin was synthesized from the reaction of 5,6-diamino-1,10-phenanthroline with antidichloroglyoxime. Polymeric complexes with Ni(II), Co(II) and Cu(II) have been obtained. The new compounds have been characterized by FTIR, H-1 NMR (DMSO-d(6)), elemental analyses and magnetic measurements. The ligand and the Ni(II), Co(II) and Cu(II) complexes have been studied potentiometrically. The metal to the ligand ratio of the Cu(II), Ni(II) and Co(II) complexes was found to be 1: 1. The Co(II), Ni(II) and Cu(II) complexes of the ligand are paramagnetic. Protonation constants of the ligand and overall formation constants of the complexes have been calculated from potentiometric data using the program TITFIT.
Keywords: METAL-COMPLEXES; CRYSTAL; LIGAND; URANYL(VI); Chemistry